International trade - Rivera-Batiz, Luis A. (Oxford University Press, 2003)
The field of international trade has been a focus of renewed debate for academics and policy-makers alike. The progressive integration of economics at a worldwide level have led to debates surrounding the migration of labor markets, restrictive trade practices, the impact of foreign investment, the role of cooperation through multilateral and regional agreements, and the enforceability of international agreements. This book reviews the new research findings and theoretical developments that have informed these debates, offering a balanced analytical account of American and European experiences, viewpoints, approaches and policy